2018
DOI: 10.1038/s41424-018-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of venous thromboembolism in hospitalized patients with cirrhosis due to non-alcoholic steatohepatitis

Abstract: ObjectivePatients with cirrhosis are at increased risk for venous thromboembolism (VTE) and portal vein thrombosis (PVT). Cirrhosis due to non-alcoholic steatohepatitis (NASH) appears to be particularly prothrombotic. We investigated hospitalized patients with NASH cirrhosis to determine if they are at increased risk for VTE.MethodsData on adult hospitalized patients with cirrhosis and VTE (deep vein thrombosis and/or pulmonary embolism) between November 1, 2010 and December 31, 2015 were obtained. Cases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 41 publications
0
57
0
1
Order By: Relevance
“…Platelet lysis in vitro has been shown to inhibit fibrinolysis . The association of NASH/cryptogenic cirrhosis with FS and postoperative venous thrombosis is supported by evidence for its prothrombotic and hypofibrinolytic predisposition, presumably due to a chronic hepatic inflammation–induced decrease in the anticoagulants protein C and antithrombin and an increase in the antifibrinolytic plasminogen activator inhibitor‐1 …”
Section: Discussionmentioning
confidence: 98%
“…Platelet lysis in vitro has been shown to inhibit fibrinolysis . The association of NASH/cryptogenic cirrhosis with FS and postoperative venous thrombosis is supported by evidence for its prothrombotic and hypofibrinolytic predisposition, presumably due to a chronic hepatic inflammation–induced decrease in the anticoagulants protein C and antithrombin and an increase in the antifibrinolytic plasminogen activator inhibitor‐1 …”
Section: Discussionmentioning
confidence: 98%
“…49 Concerning the impact of thrombocytopenia, one report indicated that thrombocytopenia was associated with decreased risk, but most studies have not identified a relationship. 50,51 Rather, the presence of thrombocytopenia is strongly associated with the development of portal vein thrombosis. 52 Given the underlying perception that patients with decompensated cirrhosis are coagulopathic, there is often suboptimal use of pharmacologic VTE prophylaxis, likely due to misconceptions about bleeding risk.…”
Section: Thromboembolic Riskmentioning
confidence: 99%
“…NAFLD is independently associated with an increased risk of abnormalities of cardiac structure and function, including cardiac rhythm disorders (mainly AF) [9,10]. Moreover, emergent data suggest NAFLD being associated with an increased risk of idiopathic VTE [11,12]. Therefore, a growing number of patients with advanced fibrosis/cirrhosis will be candidate for anticoagulant therapy in the near future.…”
mentioning
confidence: 99%